Miasto, barrios i kultura popularna w Peru – tożsamość kulturowa nowych mieszkańców Limy - Górska, Katarzyna (2020)
CITY, BARRIOS AND POPULAR CULTURE IN PERU – CULTURAL IDENTITY OF LIMA’S NEW INHABITANTSMassive rural-urban migration contributed to Peru’s cultural transformation. Since the 1940s migrants from the provinces were arriving to the country’s capital. In the 21th century the numbers are much changed from what they were in the second half of the 20th century. Yet, Lima still has one of the highest levels of immigra- tion in Peru. Along with the demographic change came the cultural one. Today four generations of migrants and their children with new cultural representations are redefining their identity, the city, and its culture. Internal migration gave rise to a new area of cultural negotiations and interpretations. Focused on concepts from cultural studies, the book explores cultural identity and popular culture of Nuevos Limeños (new inhabitants of Lima), most of whom are of migrant origin. The book’s main objectives are: Firstly, to describe changes that determine inhabitants’ contemporary identity based on the cultural level of analysis. Secondly, to distinguish cultural forms that today serve as identity manifestations of Nuevos Limeños. And finally, to approach possible interpretation of identity changes and analyze what these new negotiations of meaning and representation imply for Lima and Peru. The text introduces readers to the theory on identity and Latin American city, indicating the most important theories to analyze urban culture and change (transculturation, hybrid culture, heterogeneidad). Subsequently, as the text brings together two levels of analysis of the city, it provides a field-research-based study of informal settlement in the metropolitan area and popular culture manifestations in middle- and upper-class districts. Popular culture with its most vibrant representations of musica chicha, popular graphics, and new urban festivities manifests cultural identity of urban migrants and their children.
Keywords: cultural identity; popular culture; urban migrants; informal settlements